Harlem Renaissance Literature Langston Hughes - Ganieva Madina Ganiboy kizi; Artikov Jasurbek Alisherovich (Peerian Journals Publishing, 2022)
Langston Hughes and the basic themes of his poetry. It is important to know about an idea of that period. Theoretical part of the work can be useful for the articles, diploma works in American Literature. The Practical value lies in as a source of preparation for lectures and seminars on American literature classes.
Keywords: Brownies Book; Crisis; Mulatto; Simple